If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -2 + i)(x + -2 + -1i) = equation Reorder the terms: (-2 + i + x)(x + -2 + -1i) = equation Reorder the terms: (-2 + i + x)(-2 + -1i + x) = equation Multiply (-2 + i + x) * (-2 + -1i + x) (-2(-2 + -1i + x) + i(-2 + -1i + x) + x(-2 + -1i + x)) = equation ((-2 * -2 + -1i * -2 + x * -2) + i(-2 + -1i + x) + x(-2 + -1i + x)) = equation ((4 + 2i + -2x) + i(-2 + -1i + x) + x(-2 + -1i + x)) = equation (4 + 2i + -2x + (-2 * i + -1i * i + x * i) + x(-2 + -1i + x)) = equation Reorder the terms: (4 + 2i + -2x + (-2i + ix + -1i2) + x(-2 + -1i + x)) = equation (4 + 2i + -2x + (-2i + ix + -1i2) + x(-2 + -1i + x)) = equation (4 + 2i + -2x + -2i + ix + -1i2 + (-2 * x + -1i * x + x * x)) = equation Reorder the terms: (4 + 2i + -2x + -2i + ix + -1i2 + (-1ix + -2x + x2)) = equation (4 + 2i + -2x + -2i + ix + -1i2 + (-1ix + -2x + x2)) = equation Reorder the terms: (4 + 2i + -2i + ix + -1ix + -1i2 + -2x + -2x + x2) = equation Combine like terms: 2i + -2i = 0 (4 + 0 + ix + -1ix + -1i2 + -2x + -2x + x2) = equation (4 + ix + -1ix + -1i2 + -2x + -2x + x2) = equation Combine like terms: ix + -1ix = 0 (4 + 0 + -1i2 + -2x + -2x + x2) = equation (4 + -1i2 + -2x + -2x + x2) = equation Combine like terms: -2x + -2x = -4x (4 + -1i2 + -4x + x2) = equation Solving 4 + -1i2 + -4x + x2 = aeinoqtu Solving for variable 'i'. Reorder the terms: 4 + -1aeinoqtu + -1i2 + -4x + x2 = aeinoqtu + -1aeinoqtu Combine like terms: aeinoqtu + -1aeinoqtu = 0 4 + -1aeinoqtu + -1i2 + -4x + x2 = 0 The solution to this equation could not be determined.
| 31-x-12=15 | | 112+7x= | | -4m^2-8m+1=5 | | 2(3x-6)=16 | | x+20+10x=10+9x | | B(x)=45.50-0.10x | | 11x-11=2x+9 | | 25x-25y=25 | | .80x+12=.3 | | 11x-24=-7 | | 4(7a-a)-38=26a-5(2+6a) | | 5a-6=4x | | 2p^2-7=7p | | 25+-55+(65+85)=5 | | 10y^2-71y+88=0 | | 80m=80 | | (2x+20)+(2x+20)+x+x=460 | | 5m-2m+9=-12 | | z^2=-3z+2 | | x^2=-12x+6 | | X+666x=0 | | 127=(2x+41) | | 7z^2+8z-5=0 | | 8x-8-6x=20 | | x=x+32 | | 6(x+5)-6=48-2x | | 5y+8=-1 | | 6(x+5)-6=48 | | 5(x-9)=7(x-3) | | 7y^2-8y-7=0 | | 3(X+2)(2x-10)=0 | | 8x^2=26x+357 |